PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR DAN KREATIVITAS PENDIDIKAN PANCASILA DI KELAS V SEKOLAH DASAR - Fadilla Nurdiana Wahyuningrum; Risma Widiawati; Susilo Tri Widodo; Wulan Aulia Azizah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The aim of the Pancasila education subject in elementary school is important because this subject is one of the basics in forming good citizens, who act in ways that are based on Pancasila which is the identity and identity of the nation. However, in its implementation, this goal cannot be achieved easily, as shown by the learning outcomes and creativity of class V students at SD Negeri 2 Girimarto, Wonogiri Regency which are still low. The research was conducted using descriptive methods with a quantitative approach. Based on data on learning outcomes, it was found that the use of the project based learning model in class V educational learning can improve the learning outcomes of class V students with an average score of 55.7143 to 91.4286. Based on the t test, it is known that the sig value. (2-tailed) (0.000) < α (0.05), which indicates that there is a significant difference between the initial and final variables or Ha is accepted and Ho is rejected. In the NGain score obtained is 0.8202, because 0.8202 > 0.7 it can be concluded that it is classified as effective. For skill scores, the average was 75.34%. This shows that learning outcomes in this skill aspect are categorized as high. Thus, the project based learning (PJBL) learning model can be an effective strategy for improving student learning outcomes and creativity.